Hubungan Usia, Pekerjaan, dan Dukungan Suami Terhadap Keikutsertaan Ibu Hamil Primigravida Pada Kelas Prenatal Yoga - Putri Ancila Citra Prasetya (Pusat Riset dan Inovasi Nasional, 2023)
Background Maternal Mortality Rate (MMR) is the main indicator for assessing the success of maternal health programs because of its sensitivity to improving health services, both in terms of accessibility and quality. Acceleration in reducing MMR can be achieved by improving health services for pregnant women in prenatal yoga classes which have the benefit of improving maternal health, both physical, mental and emotional. The aim of this research is to determine the relationship between maternal age, maternal employment and husband's support on maternal participation in prenatal yoga classes. Methode This research method is quantitative research with a cross sectional approach. The subjects were 42 primigravida. The sampling used was consecutive sampling. Data were collected using a questionnaire list, then the data was processed using the Chi Square test. Result The results of the bivariate test using the chi square test showed that there was a significant relationship between husband's support (p value = 0.009), there was no significant relationship between mother's age (p value = 0.559) and mother's employment (p value = 0.525) with the participation of primigravida pregnant women in taking prenatal yoga classes. Conclussion Husband's support is associated with mother's participation in prenatal yoga classes.